Optimalisasi Perencanaan Diversifikasi Usaha Bunga Potong - Ni Putu Darmayanti; I Gusti Ngurah Apriadi Aviantara; Ida Bagus Putu Gunadnya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
The aims of this research were to determine the profit of each type of cut flower and to identify the types of cut flowers that should be produced to maximize profit in the diversification of flower business development. The research methods used included cost analysis, profit margin analysis, and the simplex method. The results showed that the production cost per stalk for each type of cut flower was Red Heliconia carabaea (Rp 498), Yellow Heliconia carabaea (Rp 456), Anthurium (Rp 316), Yellow Dancer (Rp 503), Hanging Chalk (Rp 578), Sexy Pink (Rp 583), Parakeet (Rp 458), Torch (Rp 496), and Onje (Rp 523), while the profit per stalk was respectively Rp 1,408; Rp 1,484; Rp 58; Rp 1,000; Rp 1,134; Rp 1,163; Rp 823; Rp 657; and Rp 429. Based on simplex method calculations, using profit margin as the objective function and production cost and market conditions as constraints, the optimal profit for business development was obtained from Red Heliconia carabaea (Rp 33,114,331), Yellow Heliconia carabaea (Rp 30,386,354), Sexy Pink (Rp 18,937,006), and Hanging Chalk (Rp 17,406,016).